Separation anxiety: stress, tension and cytokinesis - Mohan, Krithika (2012)
Cytokinesis, the physical separation of a mother cell into two daughter cells, progresses through a series of well-defined changes in morphology. These changes involve distinct biochemical and mechanical processes. Here, we review the mechanical features of cells during cytokinesis, discussing both the material properties as well as sources of stresses, both active and passive, which lead to the observed changes in morphology. We also describe a mechanosensory feedback control system that regulates protein localization and shape progression during cytokinesis.